Vanadium-Containing Anionic Chelate for Spectrophotometric Determination of Hydroxyzine Hydrochloride in Pharmaceuticals - Gergana Kirilova Kirova; Zdravka Yancheva Velkova; Vassil Borisov Delchev; Kiril Blazhev Gavazov (Molecules, 2023)
Four azo dyes known to form anionic complexes with V(V) were investigated as potential liquid–liquid extraction–spectrophotometric reagents for the antihistamine medication hydroxyzine hydrochloride (HZH). A stable ion-association complex suitable for analytical purposes was obtained with 6-hexyl-4-(2-thiazolylazo)resorcinol (HTAR). The molar absorption coefficient, limit of detection, linear working range, and relative standard deviation in the analysis of real pharmaceutical samples (tablets and syrup) were 3.50 × 104 L mol−1 cm−1, 0.13 μg mL−1, 0.43–12.2 μg mL−1, and ≤2.7%, respectively. After elucidating the molar ratio in the extracted ion-association complex (HZH:V = 1:1), the ground-state equilibrium geometries of the two constituent ions—HZH+ and [VO2(HTAR)]−—were optimized at the B3LYP level of theory using 6-311++G** basis functions. The cation and anion were then paired in four different ways to find the most likely structure of the extracted species. In the lowest-energy structure, the VO2 group interacts predominantly with the heterochain of the cation. A hydrogen bond is present (V–O···H–O; 1.714 Å) involving the terminal oxygen of this chain.